2017
DOI: 10.3389/feduc.2017.00056
|View full text |Cite
|
Sign up to set email alerts
|

School Belonging in Different Cultures: The Effects of Individualism and Power Distance

Abstract: Limited evidence exists on how the larger cultural framework affects psychological processes related to schooling. We investigated how the cultural dimensions of individualism/collectivism and power distance influence the sense of school belongingness using 2003 Programme for International Student Assessment survey data on 15-year-old students from 31 countries. Hierarchical linear modeling analysis indicated that power distance (i.e., hierarchical nature of social relationships) is a better predictor of schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 64 publications
5
67
1
Order By: Relevance
“…There is still limited evidence on how the broader cultural factors affect psychological processes related to schooling. However, the existing studies suggest that the cultural dimensions of individualism/collectivism and power distance may influence functioning in school (Cortina, Arel, & Smith-Darden, 2017), and potentially later during studies. A cross-cultural investigation of study addiction in Asian cultures should arguably include the role of such factors as filial piety, found to be related to academic performance in previous studies (Yeh & Bedford, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…There is still limited evidence on how the broader cultural factors affect psychological processes related to schooling. However, the existing studies suggest that the cultural dimensions of individualism/collectivism and power distance may influence functioning in school (Cortina, Arel, & Smith-Darden, 2017), and potentially later during studies. A cross-cultural investigation of study addiction in Asian cultures should arguably include the role of such factors as filial piety, found to be related to academic performance in previous studies (Yeh & Bedford, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in line with stage-environment fit theory, students in performance-oriented learning environments, focused on the demonstration of performance, tend to put emphasis on the evaluation of the self, thus increasing social comparison and self-focus (Kumar 2006;Meece et al 2006). In keeping with this, Cortina et al (2017) show that Asian countries, focused on competitive testing and demonstration of relative ability, have lower school belonging. Research showing that performance-orientation is positively related with test anxiety (von der Embse et al 2018), and that high-stakes testing has negative effects on school belonging (Markowitz 2018;Plank and Condliffe 2013), are also in line with theoretical predictions.…”
Section: Previous Empirical Research On School Belongingmentioning
confidence: 85%
“…The items capture worries in relation to academic performance and evaluation (e.g. grades and homework), and indirect theoretical as well as empirical work suggest that evaluative and performance-oriented environments lead to intensified social comparison and self-focus (Cortina et al 2017;Eccles and Roeser 2011;Kumar 2006;von der Embse et al 2018). The index is constructed from four Likert items of the type "I worry that I will get poor grades in mathematics", with response options ranging from "Strongly disagree" (0) to "Strongly agree" (3).…”
Section: Independent Variablesmentioning
confidence: 99%
“…Many students value shadow education teachers more than those in public schools, believing that shadow education teachers are more understanding, more patient, and provide better guidance than schoolteachers (Kim & Jung, 2019). In Thailand, the high-power distance due to Thai culture norm revealed that teachers are respected figures and are seen to be infallible, which made the student-teacher relationship somehow distanced so that students do not approach teachers for questions (Cortina et al, 2017). As such, low-performance students in mainstream schools are forced into a denigrated relationship with their schoolteachers.…”
Section: Journal Of Educational Issuesmentioning
confidence: 99%